2023
DOI: 10.1002/anie.202315357
|View full text |Cite
|
Sign up to set email alerts
|

Probing Degradation in Lithium Ion Batteries with On‐Chip Electrochemistry Mass Spectrometry**

Daisy B. Thornton,
Bethan J. V. Davies,
Soren B. Scott
et al.

Abstract: The rapid uptake of lithium ion batteries (LIBs) for large scale electric vehicle and energy storage applications requires a deeper understanding of the degradation mechanisms. Capacity fade is due to the complex interplay between phase transitions, electrolyte decomposition and transition metal dissolution; many of these poorly understood parasitic reactions evolve gases as a side product. Here we present an on‐chip electrochemistry mass spectrometry method that enables ultra‐sensitive, fully quantified and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…This includes experiments in full cells and with a reference electrode, [72,136] experiments where a correct electrolyte-to-active material ratio limits the amount of conductive salt and electrolyte available for degradation reactions, i. e. measurements in larger cell formats, [137,138] and a reliable and precise quantification and separation of both HCN and (CN) 2 , which may be achieved by novel DEMS cell designs, such as onchip electrochemistry-mass spectrometry (EC-MS). [139] To better understand follow-up reactions, we envision that labeling the PW CAM with 13 CN may allow for the detection of gaseous products via DEMS/OEMS and electrolyte side products via 13 C nuclear magnetic resonance (NMR) spectroscopy. Overall, the findings highlight the importance of gas evolution measurements for an exhaustive characterization of battery materials, and the effect of coating, doping, additives, synthesis, and processing procedures on suppression of (CN) 2 evolution may become a new field of consideration in PBA/PW research.…”
Section: Discussionmentioning
confidence: 99%
“…This includes experiments in full cells and with a reference electrode, [72,136] experiments where a correct electrolyte-to-active material ratio limits the amount of conductive salt and electrolyte available for degradation reactions, i. e. measurements in larger cell formats, [137,138] and a reliable and precise quantification and separation of both HCN and (CN) 2 , which may be achieved by novel DEMS cell designs, such as onchip electrochemistry-mass spectrometry (EC-MS). [139] To better understand follow-up reactions, we envision that labeling the PW CAM with 13 CN may allow for the detection of gaseous products via DEMS/OEMS and electrolyte side products via 13 C nuclear magnetic resonance (NMR) spectroscopy. Overall, the findings highlight the importance of gas evolution measurements for an exhaustive characterization of battery materials, and the effect of coating, doping, additives, synthesis, and processing procedures on suppression of (CN) 2 evolution may become a new field of consideration in PBA/PW research.…”
Section: Discussionmentioning
confidence: 99%
“…The SEI can prevent further decomposition of electrolyte, suppressing additional outgassing. Thornton et al 341 found that substantially more CO and C 2 H 4 are evolved in the first cycle. The non-negligible amount of evolved gas in the following cycles suggests that the graphite surface is not entirely passivated after one cycle (see Fig.…”
Section: Applicationsmentioning
confidence: 99%